Long-term results of palatal implants for primary snoring - Maurer, Joachim T.; Hein, Gerhard; Verse, Thomas; Hörmann, Karl; Stuck, Boris (Otolaryngology - head and neck surgery, 2005)
OBJECTIVE: To determine the safety and efficacy of the Pillar Palatal Implant System over a 1-year follow-up period., STUDY DESIGN AND SETTING: In this prospective study, 40 healthy adult patients with primary snoring due to palatal flutter were treated after clinical, polysomnographic, and endoscopic examination. Under local anesthesia 3 implants were placed into the soft palate. Postoperative morbidity and functional parameters were assessed. Snoring and daytime sleepiness were assessed before and 90, 180, and 360 days after surgery. Objective data were obtained by polysomnography and SNAP-recording before and 90 days after treatment., RESULTS: All implants were placed without complications. A total of 13 implants partially extruded uneventfully in 10 patients. Functional parameters remained unchanged. After 1 year, snoring was reduced from 7.1 ± 1.9 to 4.8 ± 2.5 (Visual-Analogue-Scale, P < 0.05) and daytime sleepiness from 6.1 ± 3.2 to 4.9 ± 3.1 (Epworth-Sleepiness-Scale, P < 0.05). SNAP data and polysomnography parameters showed clinically irrelevant changes., CONCLUSION: Our data demonstrate a significant decrease in snoring and daytime sleepiness over a period of one year.